استراتيجيات حفظ القرآن الكريم لدى الحفّاظ فى مؤسسة التحفيظ دار القرآن، ماليزيا :‏ ‏دراسة حالة /‏ - Nik Md Saiful Azizi bin Nik Abdullah (Ma'had al-Tarbiyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
The Holy Quran holds a very high position in the minds of Malaysian Muslims. This study aims at investigating Quranic memorization strategies used by the memorizers under Darul Quran Institution at the Department of Islamic Affairs (JAKIM) in Malaysia. The main question posed by the study is “What are the most unique Quranic strategies employed by the memorizers to master Quranic memorization?” In order to answer this question, the researcher selected five strong and five weak memorizers from Darul Quran using semi-structured interview. The researcher utilized ATLAS.ti to analyze the data collected from the interview sessions. Based on the data analysis, the following results are found; those memorizers suggested seven perceptions towards the mastery of Quran, they encountered challenges of memorization and difficulty to recall of the verses memorized. Constant repetition is an effective strategy for memorizing the Quran as said by the strong memorizers. The study suggested the improvement of students' perception towards Quranic memorization by using mental excitement strategies and counseling them on how to overcome the problems through self determination. The study also offered suggestions to the authority to identify effective strategies which might help both strong and weak students to improve their Quranic memorization skills.